Improving students’ scientific literacy through a problem-based learning model integrated with socio-scientific issues on ecosystem learning - Khairrunisa, Agustina Nur; Yusup, Iwan Ridwan; Paujiah, Epa (Universitas Negeri Jakarta, 2025)
Scientific literacy is recognized by the World Economic Forum as one of the 16 essential skills for the 21st century. However, the scientific literacy of Indonesian students remains relatively low based on PISA results. This study aims to examine the enhancement of students' scientific literacy through implementation of Problem Based Learning (PBL) model based on socio-scientific issues (SSI) on ecosystem learning. This research used a quasi-experimental study with a non-equivalent control group design. The population consisted off all 7th grade in the academic year 2024/2025, totaling 108 students. Two classes were selected as samples: 28 students in the experimental class and 26 students in the control class. Data collection instruments include tests, observation, and questionnaire. The data were analyzed using N-Gain to measure improvement and inferential statistics to test significance. These findings suggest that Problem Based Learning (PBL) based on socio-scientific issues (SSI) effectively enhances students' scientific literacy. This research can be an alternative strategy, and reference for teachers and schools in implementing innovative learning that supports scientific literacy development.